The impact of perceived quality of online interaction on satisfaction of international student interactions in higher education - Wang, Xiaozhuan; Hassan, Aminuddin Bin; Shwu Pyng, How; Ye, Han; Aminuddin, Ain Afiqah (Informa UK Limited, 2024)
Online learning is a necessary teaching method for higher education institutions to cope with future unpredictable events. This study aims to investigate the impact of four forms of perceived quality in online interaction on the satisfaction of international students. The four types of online interaction considered are Teacher-Student Interaction (TSI), Student-Student Interaction (SSI), Student-Content Interaction (SCI), and Student-Interface Interaction (SII). Employing a quantitative research approach, we used a questionnaire for data collection in the investigation. The questionnaire underwent rigorous assessment for reliability and validity. The population of this study consists of a university in Zhejiang Province, China, with over 2,000 international students enrolled in 2019. Utilizing a stratified random sampling technique, we selected 320 international students exclusively participating in 100% online courses. Data analysis, conducted using SPSS 26.0, included descriptive analysis, correlation analysis, and multiple linear regression analysis. The research findings underscore the critical role of the perceived quality of three types of interactions—TSI, SSI, and SCI—in influencing student satisfaction with online learning interactions. This study contributes to enriching research on international student satisfaction with online interaction, providing valuable insights for educators and institutions aiming to enhance the quality of online learning experiences.